e-LEADERSHIP: Faktor Kunci Pengembangan Kapasitas Teknologi Informasi dan Komunikasi di Daerah - Anwaruddin, Awang (Jurnal Borneo Administrator, 2009)
Leadership is not limited to a position or job; it is a worldview      and a way of being in the world. It takes vision and imagination as well as knowledge, to be a leader. We define leadership as the ability to bring people, tools and resources together to solve problems and achieve results. In the world today, we need to bring people together across national, geographic, cultural and other boundaries, using communications technologies tools to achieve results. e-Leadership means a balancing many roles and carrying them out via communications technologies.               Thus,  e-Leadership is no different from any other form of effective leadership  except that in e-leadership you have no option but to be very good at it. It  requires a high level of transformational leadership because of the highly  participative nature of the e-world between e-organisations and e-customers and  the interconnectedness between leader and follower with the ever-increasing  reality of the blurred lines between the two (Robert Burke: 2008). Key Word: e-Leadership, e-Government, Kepemimpinan transformasional,  Virtual    tim, Komunikasi multilevel, Profesionalitas